Leaf Damaged by Nymph of Cardiaspina albitextura and Cardiaspina retator (Hemiptera: Psyllidae) - NISMAH NISMAH (HAYATI Journal of Biosciences, 2008)
Cardispina (Hemiptera: Pshyllidae) is one of the most important genera of the Australian Psyllidae, owing to the spectacular damage to Eucalyptus spp. The increase of C. albitextura and C. retator populations in high numbers caused severe damage on leaves of Eucalyptus camaldulensis. Both species have similarities, i.e. they occur on the same host plant and prefer mature leaves of E. camaldulensis for oviposition and feeding sites. They might thus be more likely to show competition than the less closely related taxa. The purpose of the study was to examine degree of the resource use by measuring the area of leaves damaged by the nymphs of C. albitextura and C. retator. The results indicated that the nymph of C. retator caused damage twice more damages than that of C. albitextura. The leaves area damaged by the females of both species was greater than that by the males. Key words: Cardiaspina, albitextura, retator, leaf, damage, nymph